(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the levels of fibrinogen and FVIII in single and multiple vessels ischemic heart disease patient’s. Study Design: Cross sectional / comparative study. Place and Duration of Study: This study was conducted at the Department of Pathology, Post Graduate Medical Institute and Punjab Institute of Cardiology, Lahore from 24th October 2014 to 20th April 2015. Materials and Methods: The study included 80 diagnosed ischemic heart disease patients who were divided into three groups, group 1 comprised of 40 patients with single vessel disease followed by group 2a with double vessel and group 2b were with multiple vessel disease. The parameters studied in these groups were risk factors like age, gender, hypertension, smoking, positive family history; number of vessels and the level of FVIII and fibrinogen and the subsequent data was recorded. Mean ± standard deviation, frequency distribution and percentages were calculated. SPSS version 20 was utilized to obtain statistical significance. Pearson’s chi-square and Fisher’s exact test were applied. Results: In the present study, there were 80 diagnosed IHD patients out of which 40 (50%) had single vessel disease and 40(50%) had double and multiple vessels disease. Mean ± SD of fibrinogen was 305.1± 56.7 with a p- value of 0.85. Mean ±SD of FVIII was 191.2 ± 48.2 with a p- value of 0.80. Conclusion: In the present study the levels of fibrinogen was raised in single vessel disease and FVIII were increased in multiple vessel disease patients. Hence it was concluded that these patients can be screened out on the basis of these two haemostatic parameters as they play a significant role in ischemic heart disease patients